2017
DOI: 10.1007/s13193-017-0716-4
|View full text |Cite
|
Sign up to set email alerts
|

Rare Case Report of Neuroendocrine Tumor in Axilla-Metastasis from Unknown Primary or De Novo?

Abstract: Neuroendocrine tumors (NET) are the neoplasm arising from neuroendocrine cells which are present throughout the body. It can be benign, being more common or malignant. Gut is the most common site, but they can be seen in any part of the body. We had a case of grade III NET in axilla presented with a fungating lesion with unknown primary. Clinical behavior of such tumor is predicted by tumor grade or differentiation. We treated this patient by surgery and adjuvant chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…There have been reported incidences of NET arising from breast tissue, abdominal wall and lymph nodes 4–7. In cases with isolated nodal/soft tissue involvement without any primary foci, the possibility of a lymph node-origin tumour based on epithelial inclusions or anomalous carcinomatous differentiation of stem cells of the lymphoreticular system can be considered 4.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reported incidences of NET arising from breast tissue, abdominal wall and lymph nodes 4–7. In cases with isolated nodal/soft tissue involvement without any primary foci, the possibility of a lymph node-origin tumour based on epithelial inclusions or anomalous carcinomatous differentiation of stem cells of the lymphoreticular system can be considered 4.…”
Section: Discussionmentioning
confidence: 99%
“…The most common sites include the gut, lungs, and bronchi; however, the soft tissue is an uncommon site [ 4 ] and is classified as NETs and neuroendocrine carcinomas (NECs) according to the latest World Health Organization (WHO) edition published in 2019 [ 11 ]. Dholaria et al [ 12 ] reported a case of NEC in the axilla of a man. IHC of this tumor showed positive Syp, and negative for CK7 and CK20, with a high Ki-67 index (80%).…”
Section: Discussionmentioning
confidence: 99%
“…IHC of this tumor showed positive Syp, and negative for CK7 and CK20, with a high Ki-67 index (80%). Therefore, he was diagnosed with NEC and axillary metastasis from an unknown primary or de novo [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…After 4 cycles, a new PET/CT showed partial metabolic response in the axillary mass and complete response of adrenal metastases, marked with blue and green arrows, respectively ( B ). Even NETs can originate from any neuroendocrine cell in the body, them originating in axillary soft tissues is very uncommon, 1–3 and the incidence of lymph node metastasis from an unknown primary NET is also low 4 . NETs commonly overexpress SSTR in grade 1 and 2 tumors; however, some series have demonstrated that grade 3 NET can also have SSTR overexpression in 61.9% of cases 5 .…”
mentioning
confidence: 99%